2019
DOI: 10.1563/aaid-joi-d-19-00076
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Stress Distribution on Mandibular Implant-Supported Overdentures With Different Bone Heights and Attachment Types: A 3D Finite Element Analysis

Abstract: The biomechanical behavior of the edentulous mandible with bone irregularities that has been rehabilitated with implant-supported overdentures has become an important factor for treatment planning. Restorative options, including dental implants with various attachments, affect the stress distribution. The purpose of this study was to evaluate the stress distribution of cortical bone around the implant neck and implant structures in overdentures with two different attachment types at the edentulous mandible and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…In the bilateral posterior loading condition, the difference between stress values in the cortical bone surrounding the implants was lower than in other loading conditions. This finding was similar to the study of Unsal et al [25]. The stress distribution pattern in the cases of bilateral loading was more evenly, so it could be recommended to consider bilateral balanced occlusion in overdentures [2,25].…”
Section: Only In the Anterior Loading Condition The Amount Of Stress ...supporting
confidence: 90%
“…In the bilateral posterior loading condition, the difference between stress values in the cortical bone surrounding the implants was lower than in other loading conditions. This finding was similar to the study of Unsal et al [25]. The stress distribution pattern in the cases of bilateral loading was more evenly, so it could be recommended to consider bilateral balanced occlusion in overdentures [2,25].…”
Section: Only In the Anterior Loading Condition The Amount Of Stress ...supporting
confidence: 90%
“…El-Anwar et al 33 stated that Locator attachments cause less stress than ball attachments. Unsal et al 10 reported that better biomechanical results were obtained in models with ball attachments. However, in both studies, the loading conditions were not suitable and the applied forces were far from imitation of the oral environment.…”
Section: A B C D E F G Hmentioning
confidence: 99%
“…16,24 At different angles of load, the behavior of an attachment in stress transmission may be different. 10,35 Therefore, in the comparison of different attachment types, occlusal forces should be applied in a way to realistically simulate chewing.…”
Section: A B C D E F G Hmentioning
confidence: 99%
See 2 more Smart Citations